Magnitude, resistance profiles, and risk factors of intestinal parasites and enteric bacteria among food handlers in West Guji Zone, Ethiopia - Lechisa Asefa; Gudeta Kumela; Habtamu Roba; Angefa Ayele; Gedeno Karbana; Degefa Dhengesu; Hailu Lemma; Anteneh Fikrie (PLoS ONE, 2026)
Introduction Despite food handlers’ crucial role in pathogen transmission, current data on intestinal parasites and antimicrobial susceptibility and resistance patterns of enteric bacteria among food establishment workers in Bule Hora town are notably limited. This knowledge gap hinders effectiveness of public health interventions. Objective This study aimed to assess the prevalence and antimicrobial resistance profile of intestinal parasites, enteric bacteria, and associated factors among food handlers in Bule Hora town food and drinking establishments. Methods We employed a cross-sectional study design to assess the health status of food handlers. Data were collected utilizing both a semi-structured questionnaire to gather self-reported information and an observational checklist to assess practices and environmental factors. A total of 375 stool samples were collected from the participating food handlers. These samples underwent laboratory examination for the identification of bacterial and parasitic pathogens. To determine factors independently associated with the health status of food handlers, multivariable logistic regression analysis was performed. Adjusted odds ratio together with 95% Confidence Interval (CI) were used to measure the association and p value < 0.05 was used to declare the statistical significance. Result Overall, 147(39.2% (95% CI: 34.26, 44.14)) prevalence of intestinal parasites and 50 (13.3%) (95%CI: 9.2–19.7) prevalence of bacteria was found in this study. The most predominant parasite was Ascaris lumbricoid (51.1%) and the most frequently reported an enteric bacterium was Salmonella 39 (78%). Out of 39 Salmonella isolates, 20.5% showed multidrug resistance, while none of the 11 Shigella isolates were multidrug resistant. From multivariable binary logistic analysis, unable to read and write (AOR = 1.96, 95% CI 1.18, 3.26), not trimming fingernails (AOR = 2.52; 95% CI: 1.20, 9.55), not washing hand with soap after toilet (AOR = 2.27, 95% CI 1.17, 4.42), and eating raw food (AOR = 1.62, 95% CI 1.39, 5.00) have a significant association with the prevalence of bacteria and parasites. Conclusion Intestinal parasites and bacteria were among the leading causes of morbidity in the study area. Educational status, eating raw vegetables or fruit, hand washing after the toilet, and fingernail trimming show significant associations with the health status of food handlers.